Asian J. Org. Med. Chem. 2017
DOI: 10.14233/ajomc.2017.ajomc-p66
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and in vitro Cytotoxic Evaluation of Some Novel Heterocyclic Compounds Bearing Indole Ring

Abstract: Reaction 1H-indole-3-carboxaldhyde 1 with thiosemicarbazide derivatives to give thiosemicarbazone derivatives 2a,b. Cyclization of thiosemicarbazone 2a with HCl, Ac 2 O, phenacyl bromides and chloroacetic acid afforded the corresponding 1,2,4-triazole-3-thiol derivative 3, diacetyl derivative 4 and 1,3-thiazole derivative 5 and 1,3-thiazolidin-4-ones derivative 6 respectively. Compound 6 undergoes a series of heterocyclization reactions to give new heterocyclic compounds. The structure of the newly synthesized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Also compounds 6 recorded relatively close MIC (5.40 μg/mL) for Pseudomonas aeruginosa microbe compared to the standard drug (4.90 μg/mL). The minimum inhibitory concentration (MIC) was considered to be the lowest concentration of the tested compound which inhibits the growth of microorganisms . It was suggested that the activity of phenothiazine derivatives against micro‐organisms is as result of interaction of pharmacophoric substituents and multicyclic ring (pi‐pi interaction, intercalation in DNA) as well as the penetration of biological membrane as result of the lipophilic character of the molecule…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also compounds 6 recorded relatively close MIC (5.40 μg/mL) for Pseudomonas aeruginosa microbe compared to the standard drug (4.90 μg/mL). The minimum inhibitory concentration (MIC) was considered to be the lowest concentration of the tested compound which inhibits the growth of microorganisms . It was suggested that the activity of phenothiazine derivatives against micro‐organisms is as result of interaction of pharmacophoric substituents and multicyclic ring (pi‐pi interaction, intercalation in DNA) as well as the penetration of biological membrane as result of the lipophilic character of the molecule…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of new derivatives of phenothiazine has been a subject of interest in our research group . The quest for new antimicrobial agents as a result of increasing resistance of antimicrobial drugs to emerging pathogens motivated the screening of newly synthesized derivatives of phenothiazine ,…”
Section: Introductionmentioning
confidence: 99%
“…Heterocyclic compounds that contain the thiosemicarbazone residue show a number of biological applications (see, for example, Salman et al, 2016;Yusuf & Jain, 2014;Abdel-Wahab et al, 2017). As part of our studies in this area, we now describe the synthesis and structure of the title solvate.…”
Section: Structure Descriptionmentioning
confidence: 99%
“…Chemically, Thiosemicarbazones are generally known as Schiff base compounds and contain azomethine (-C=N-) group (Mohan et al, 2018). In the presences, azomethein group thiosemicarbazones are intermediate and form heterocyclic compounds (Salman et al, 2017) with suitable agents and also forms, metal complexes (Suvarapu et al, 2012) with metal ions due to in the presence of N and S donor atoms. The derivatives of thiosemicarbazones in organic and metal bonding compounds are of high biological importance.…”
Section: Introductionmentioning
confidence: 99%